1993
DOI: 10.3181/00379727-202-43516
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Taurine Levels on Liver Lipid Metabolism: An In Vivo Study in the Rat

Abstract: Previous studies using guinea pigs and cats have shown that liver lipid composition is affected by intrahepatic taurine levels. The purpose of the present study was to determine whether this sulfonated amino acid could also affect lipid metabolism in the rat, an animal capable of synthesizing substantial amounts of taurine and used extensively in studies on lipid metabolism. Wide variations in the hepatic taurine content were induced by administering either 1% taurine or 1% guanidinoethane sulfonate in the dri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
15
0
2

Year Published

1998
1998
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 21 publications
4
15
0
2
Order By: Relevance
“…A previous study showed that a high-taurine diet had no effect on appetite, food consumption, or weight gain [15], which was also confirmed by this study. In our study, there was no significant difference between the taurine treatment group and the model group in weight gain.…”
Section: Discussionsupporting
confidence: 88%
“…A previous study showed that a high-taurine diet had no effect on appetite, food consumption, or weight gain [15], which was also confirmed by this study. In our study, there was no significant difference between the taurine treatment group and the model group in weight gain.…”
Section: Discussionsupporting
confidence: 88%
“…It has been reported that the addition of taurine to cholesterol-enriched diets as compared to those without taurine leads to a marked reduction in the concentration of cholesterol in the rat liver, especially cholesterol ester [11,12,26]. In the present studies, we confirmed that dietary taurine consistently lowered the hepatic concentrations of cholesterol ester, but not free cholesterol, in both strains of rats fed the high-cholesterol diets.…”
Section: Discussionsupporting
confidence: 80%
“…The high serum triglyceride levels in the alcohol + taurine treated animals suggests that triglycerides were either secreted out of the liver (Yan et al, 1993) or that extrahepatic sources were being mobilized. However, in the alcohol + taurine treated animals, the increased concentration of plasma triglyceride could be a consequence of increased hepatic release of lipoproteins in these animals (or increased mobilization from adipose tissue).…”
Section: Discussionmentioning
confidence: 99%